Paciente masculino de 22 años de edad con Síndrome de Down y obesidad. - Ramírez Moncerrate, Luis Fabián (2020)
Down Syndrome is a disease that is produced by a variation of the chromosome gene, due to a replica of chromosome 21, increasing to 47 in the baby; Healthy lifestyles and diet play a very important role in improving the health condition of these people; Obesity is one of the most common problems in patients with Down Syndrome. Excess visceral fat increases the risk of suffering from a metabolic disease when proper medical or nutritional control is not followed; The present study is about a 22-year-old young adult who was born with Down syndrome problems; Family history mother with Congestive Heart Failure, father with uncontrolled Arterial Hypertension; The nutritional evaluation was carried out, reflecting a BMI of 30.8 Obesity Grade I with moderate cardiovascular risk; His biochemical evaluation indicated, hypercholesterolemia and hypertriglyceridemia; His normal clinical evaluation without novelty; His dietary assessment reflected an excess consumption of sugars and saturated fats, so the doctor refers him to the nutrition service for consultation because obesity is a health problem that can be corrected through healthy lifestyles. An individualized nutritional intervention plan is carried out for the patient with Down Syndrome and Grade I Obesity, where the family members are explained the guidelines and recommendations that they should follow to improve the patient's health condition; A normocaloric diet was prescribed, low in saturated fat, high in fractionated fiber in 5 meal times with the aim of reducing excess body weight and preventing future complications.